(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This study is dedicated to investigating hyperuricemia and its associated renal dysfunction mechanisms. Hyperuricemia, characterized by elevated uric acid levels, induces oxidative stress, inflammation, and tubulointerstitial injury. In addition, activation of the renin-angiotensin-aldosterone system (RAAS) exacerbates glomerular and tubular damage, leading to proteinuria, interstitial fibrosis, and glomerulosclerosis. Experimental and clinical studies demonstrate that lowering uric acid levels and modulating RAAS can prevent the decline in kidney function and slow the progression of chronic kidney disease. The results of this work can be applied in the treatment and prevention of patients with hyperuricemia, as well as in guiding clinical management strategies.